2015
DOI: 10.11648/j.ajls.s.2015030102.15
|View full text |Cite
|
Sign up to set email alerts
|

The Embryonic Development of Great Ramshorn Planorbarius Corneus under the Hypomagnetic Field

Abstract: The effect of a 100-300-fold attenuated geomagnetic field on the embryonic development of great ramshorn Planorbarius corneus and oxidation-reduction properties in water environment were studied in a hypomagnetic chamber. Mainly the hypomagnetic field effected beneficial influence on the development of mollusks: teratogenic effects were less massive, i.e. embryos that first occurred in hypomagnetic conditions were characterized by low death rate. The mobility index increased in embryos on the stage of late vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Effect of surrounding near-Earth space on biological objects changes in essential manner, it must inevitably accompany with the alteration of inner medium of bio-objects which basis consists of water. In model experiments we have established [1][2][3][4][5][6] the changing of water oxidation-reduction properties under the effect of environment factors (electromagnetic background, ionized radiation (IR), hypomagnetic field (HMF), volcano eruption and Sun eclipse). It is well-known that the concentration of water molecules in cells exceeds in 2 -3 sequence, the concentration of protein and other molecules in cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Effect of surrounding near-Earth space on biological objects changes in essential manner, it must inevitably accompany with the alteration of inner medium of bio-objects which basis consists of water. In model experiments we have established [1][2][3][4][5][6] the changing of water oxidation-reduction properties under the effect of environment factors (electromagnetic background, ionized radiation (IR), hypomagnetic field (HMF), volcano eruption and Sun eclipse). It is well-known that the concentration of water molecules in cells exceeds in 2 -3 sequence, the concentration of protein and other molecules in cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…In previous investigations of our laboratory [1][2][3] showed that water possesses unusual sensitivity to the least hardly distinсt manifеstations of solar activity. Besides, water medium is undergoing direct action of gelio-physical factors.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, water medium is undergoing direct action of gelio-physical factors. So, in model experiments [1][2][3][4][5] changing of oxidation-reduction properties of water under the effects of environment factors ("electromagnetic" background, ionized radiation, hypomagnetic field (HMF), under eruptions of volcano, solar eclipse) was established. Effect of surrounding near-Earth space on biological objects changes must inevitably accompany with the alteration of inner medium of bio-objects which basis consists of water.…”
Section: Introductionmentioning
confidence: 99%
“…And, although geomagnetic field doesn't stay constant both to induction and to configuration [1], its sharp changing isn't the factor of natural selection, animal reaction on it isn't fast genetically and can be the most diverse. Our previous investigations showed the influence of hypomagnetic field (HMF) on the embryonic development of great ramshorn Planorbarius corneus [2]. Another important factor is Ionized Radiation (IR) of the different types.…”
Section: Introductionmentioning
confidence: 99%
“…The question about the ratio of the influences on organism direct effect of IR and influence of changing environment due to this factor is not clear [9]. Earlier model experiments [2] [10] [11] were by established changing oxidation-reduction properties of water under the effects of environment factors ("electromagnetic" background, IR, HMF, under eruptions of volcano, solar eclipse). Proceed from these ideas, it is logically to investigate, how water properties change under the effect of character for cosmic flight low doses of IR and another factor of cosmic spaceweakening geomagnetic field and also their combined action.…”
Section: Introductionmentioning
confidence: 99%